Lessons Learned from Building Smart Cities: A Systematic Literature Review of Case Studies in Singapore and Seoul - Dasmond Tan; Johan Setiawan; Sheera Anela; Shyfa Ariesta Rustian (G-Tech: Jurnal Teknologi Terapan, 2024)
This systematic literature review explores the characteristics and criteria essential for smart city development. The study adheres to the guidelines outlined in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) framework and employs a meticulous approach to select relevant articles from the Scopus database. The inclusion criteria ensure that all selected articles were published between 2019 and 2023, are written in English, and originate from journals ranked within the Q1-Q4 quartiles of Scopus, thus guaranteeing the quality and relevance of the reviewed literature. This review probes into how the characteristics of residents and infrastructure motivate cities to develop their smart city initiatives. The study elucidates how technology digitizes various city aspects. Findings from the reviewed articles provide comprehensive insights into city development, integrating Information and Communication Technology (ICT), governance, and citizen participation in the process.